Implementer-Led Evaluation and Learning (IMPEL) evaluation of SPIR II RFSA - Midline survey report - Gilligan, Daniel O.; Hirvonen, Kalle; Leight, Jessica; Tesfaye, Haleluya (Implementer-Led Evaluation & Learning Associate Award, 2024)
The objective of this report is to present results from the midline survey conducted as part of the IMPEL evaluation of SPIR-II, a randomized controlled trial launched in 2022. The second phase of the Strengthen PSNP Institutions and Resilience (SPIR-II) project aims to enhance livelihoods, increase resilience to shocks, and improve food security and nutrition for rural households vulnerable to food insecurity in Ethiopia. The project is situated within Ethiopia’s Productive Safety Net Program (PSNP), one of the largest safety net programs in Africa. Funded by USAID’s Bureau for Humanitarian Assistance (BHA), SPIR-II is implemented by World Vision International (lead), CARE, and ORDA in the Amhara and Oromia regions of Ethiopia.